ORIGINAL, EUROPEAN AND JEWISH-CHRISTIAN PEOPLES ORIGIN MYTHS: : AN EXERCISE OF ANALYSIS - Cardizi, Gabriella (Revista Gênero e Interdisciplinaridade, 2021)
Analyzing origin myths of different peoples requires, above all, a historical awareness that guarantees equity of relevance to those who were subjugated to others, who, in turn, were stimulated by the overpowering of silencing discourses manifested through multiple marks of violence. The objective of the work that follows is, in addition to presenting and analyzing myths of the origins of Native American, European and Judeo-Christian indigenous peoples, to signal the unrecognized African contribution to the formation of these indigenous peoples, due to the concrete population bias, as well as the intrinsic cultural heritage demonstrated in these myths.